Investigation of the effects of benznidazole on the salivary glands: A biochemical, morphological, and functional approach - Emanuelly Camilly Soares de Lima-da-Silva; Wallacy Watson Pereira Melo; Paulo Fernando Santos Mendes; Cristian dos Santos Pereira; José Mario Matos-Sousa; Cristian Kallahan Silva Chagas; Hannah Gil de Farias Morais; Roseana de Almeida Freitas; Antonio Hernandes Chaves-Neto; Rafael Rodrigues Lima (PLoS ONE, 2025)
This study aimed to evaluate the possible biochemical effects of the administration of benznidazole on the parotid and submandibular salivary glands and saliva of rats, as well as on salivary components for the first time. Male Wistar rats (Rattus norvegicus), 66-days-old, weighing approximately 250 g were randomized into two groups: control, administered distilled water by gavage and benznidazole, administered benznidazole at a dose of 19.6 mg/kg daily by gavage over 15 days. On the 16th day, the animals were anaesthetized and the parotid and submandibular salivary glands and saliva were collected for oxidative biochemistry and morphometric analyses, and the biochemical composition of the saliva was also assessed. On the 16th day, the animals were anesthetized and their pilocarpine-induced saliva was collected. They were then euthanized to collect the parotid and submandibular salivary glands for oxidative biochemical and morphometric analyses, and the biochemical composition of the saliva was also assessed. Shapiro–Wilk normality analysis and Student’s t-test was used for parametric data and non-parametric data, respectively, with a significance of p < 0.05. The oxidative biochemical results revealed a reduction in the antioxidant capacity of the parotid and submandibular glands in benznidazole group. Morphometric analyses revealed an increase in the average area of the acini in both glands and a reduction in the stromal area of the parotid gland in the benznidazole group. Salivary analyses demonstrated a decrease in antioxidant levels and an increase in pro-oxidant levels in the group exposed to benznidazole. Total proteins, amylase, and mucin levels reduced in the exposed group. Thus, administration of benznidazole conclusively caused biochemical alterations in the antioxidant and morphological capacities of the salivary glands, followed by biochemical and protein alterations in the saliva, highlighting the possible damage caused by the drug in patients during the treatment of Chagas disease.